Effects of board density and resin content on the strength and dimensional properties of particleboard from Kelempayan (Anthocephalus Chinensis) / Shaikh Abdul Karim Yamani, Jamaludin Kasim and Ashaari Abdul Jalil - Yamani, Shaikh Abdul Karim; Kasim, Jamaludin; Abdul Jalil, Ashaari (Universiti Teknologi MARA Cawangan Pahang, 2007)
Kelempayan was successfully used in the manufacturing of urea formaldehyde particleboard at varying target board densities (525 kg/m3, 575 kg/m3 and 665 kg/m3), resin content (6%, 8% and 10%) with a board thickness of 12 mm. Increasing densities increases all the board properties significantly in a linear fashion except for internal bond. An increase in resin content results in a significant effect on all the board properties. Modulus of rupture (MOR) increases in a definite trend, internal bond and screw withdrawal (SW) shows no trend while thickness swelling (TS) decreases. Boards with density of over 600 kg/m3 and a resin content of 10% meets the minimum requirements for the strength properties as stipulated in the BS Standards (BS 5669). However, all boards fail in the thickness swelling.